Quantum image processing in practice : a mathematical toolbox - Grigoryan, Artyom; Agaian, S. S. (John Wiley & Sons, Inc., 2025)
"Image processing represents a critical use of artificial intelligence in various applications, including biomedicine, entertainment, economics, and industry. For example, image processing is extensively used in fast-growing markets like facial recognition and autonomous vehicles. Recently, the rapidly increased volume of image data has become the critical driving force for further improving image processing and analysis efficiency. Quantum computing offers great promise for speedy computation of problems in digital image processing (DIP), namely in processing grayscale and color images. Quantum image processing (QIP) is a research branch of quantum information and quantum computing. It studies how to use quantum mechanics' properties to represent images in a quantum computer and then implement various image operations based on that image format."-- Provided by publisher.
Keywords: Image processing -- Digital techniques.; Quantum computing.; elektronické knihy; electronic books